FAST Polarization Mapping of the Supernova Remnant VRO 42.05.01 - Li Xiao; Ming Zhu; Xiao-Hui Sun; Peng Jiang; Chun Sun (The Astrophysical Journal, 2023)
We have obtained the polarization data cube of the supernova remnant (SNR) VRO 42.05.01 at 1240 MHz using the Five-hundred-meter Aperture Spherical Radio Telescope (FAST). Three-dimensional Faraday synthesis is applied to the FAST data to derive the Faraday depth spectrum. The peak Faraday depth map shows a large area of enhanced foreground rotation measure (RM) of ∼60 rad m ^−2 extending along the remnant’s “wing” section, which coincides with a large-scale H i shell at −20 km s ^−1 . The two depolarization patches within the “wing” region with RMs of 97 rad m ^−2 and 55 rad m ^−2 coincide with two H i structures in the H i shell. Faraday screen model fitting on the Canadian Galactic Plane Survey 1420 MHz full-scale polarization data reveals a distance of (0.7–0.8) d _SNR in front of the SNR with enhanced regular magnetic field there. The highly piled-up magnetic field indicates that the H i shell at −20 km s ^−1 could originate from an old evolved SNR.